2007
DOI: 10.1080/02678290701407185
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical tuning capability of cholesteric liquid crystal cells containing chiral dopants end capped with menthyl groups

Abstract: 2007) Photochemical tuning capability of cholesteric liquid crystal cells containing chiral dopants end capped with menthyl groups, Liquid Crystals, 34:7, 891-902,In order to investigate the photochemical tuning capability of chiral monomers and polymers containing end-capped menthyl groups, a new series of chiral dopants was synthesized and added to commercially available nematic liquid crystals to induce cholesteric liquid crystal (LC) phases. The addition of chiral dopants with azo structure led to phototun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Taking into account that the molecular shape for cis isomers of 3,3 -disubstituted azobenzenes (rod-like) and 4,4 -disubstituted azobenzenes (bent) is different, these results strongly support the theory that the pitch changes are related to the order parameter affected by the photoisomerization of azobenzene molecules. The multiple dopants system may also contain photoresponsive chiral dopants and non-photoresponsive codopants [32,82,96,97,[105][106][107][108][109][110]. In these systems, the pitch lengths are determined by the HTPs of both dopants, and the photoresponsive dopant has the additional function of photosensitization.…”
Section: Multiple Dopantsmentioning
confidence: 99%
“…Taking into account that the molecular shape for cis isomers of 3,3 -disubstituted azobenzenes (rod-like) and 4,4 -disubstituted azobenzenes (bent) is different, these results strongly support the theory that the pitch changes are related to the order parameter affected by the photoisomerization of azobenzene molecules. The multiple dopants system may also contain photoresponsive chiral dopants and non-photoresponsive codopants [32,82,96,97,[105][106][107][108][109][110]. In these systems, the pitch lengths are determined by the HTPs of both dopants, and the photoresponsive dopant has the additional function of photosensitization.…”
Section: Multiple Dopantsmentioning
confidence: 99%
“…In another article, it was reported that the steric hindrance and molecular arrangement of chiral segments affect the physical properties of photoresists [19][20][21]. In studying the steric effects on the induction of cholesteric liquid-crystals, we synthesized a series of chiral dopants and chiral monomers [22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that reflection colors from the cholesteric phase can be reversibly tuned by external stimuli such as temperature, force, light exposure or electric fields. [4][5][6] In addition, azobenzene photochirals with two chiral centers have been synthesized to control the reflection color. [1] Azobenzene is famous as an excellent photochromic molecule due to its thermal stability, photoreversibility as well as easily resolved isomers.…”
mentioning
confidence: 99%
“…Among them, light exposure is particularly attractive due to its advantages of remote, spatial, and temporal control. [4][5][6] In addition, azobenzene photochirals with two chiral centers have been synthesized to control the reflection color. As such, it is not unexpected a much work in the area of dynamic color-control is focused on azobenzene chromophores.…”
mentioning
confidence: 99%
See 1 more Smart Citation